2011
DOI: 10.4236/jep.2011.25067
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Environmental Impact Quotient to Estimate Health and Environmental Impacts of Pesticide Usage in Peruvian and Ecuadorian Potato Production

Abstract: Currently there is no effective mechanism for measuring the potential benefits of integrated pest and disease interventions in terms of reducing pesticide risks in potato production

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 23 publications
0
13
0
1
Order By: Relevance
“…In Ecuador, the use of EBDC fungicides, and in particular the use of mancozeb, is common in the production of potatoes (Kromann et al 2011; Orozco et al 2007; Schutz 2014). Potato consumption is high in Ecuador, especially in the mountain regions, such as the Pichincha Province, where our study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In Ecuador, the use of EBDC fungicides, and in particular the use of mancozeb, is common in the production of potatoes (Kromann et al 2011; Orozco et al 2007; Schutz 2014). Potato consumption is high in Ecuador, especially in the mountain regions, such as the Pichincha Province, where our study was conducted.…”
Section: Discussionmentioning
confidence: 99%
“…The development and diffusion of integrated pest (and disease) management (IPM) knowledge and technologies is needed in order help to reduce the damage caused by pests and diseases, while also reducing dependency on hazardous pesticides (Kromann et al 2011) and promoting environment health protection. Thus, technologies such as the use of potato cultivars with resistance to pests and diseases, biological control, and alternative management practices are being advocated for to reduce the overall need for insecticides and the complete avoidance of highly toxic insecticides currently applied to control of potato pests (Kromann et al 2011, Mala et al 2012, Paredes 2010). …”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…Evaluation of the pesticide eco-toxicology could be carried out by various indexes, such as the Environmental Impact Quotient (EIQ), the Environment Risk Index (ERI) from the Quebec-NIPH (National Institute of Public Health), or the Pesticide Environmental Impact (IPEST). EIQ has been used in tropical developing countries, on the potato (Kromann et al 2011), and cruciferous vegetables (Badenes-Perez 2006). Bues et al (2004) have shown an increase in the EIQ and IPEST on tomato in tropical areas (Reunion Island) compared to Mediterranean areas.…”
Section: Environmentmentioning
confidence: 99%